Pengaruh Model Pembelajaran Game-Base Learning terhadap Hasil Belajar Siswa pada Materi Peluang - Rivaldy P.Kembau; Vivian E. Regar; Jorry F. Monoarfa (Departement of Mathematics Education, 2023)
This research aims to find out the difference in student learning outcomes applied to the GBL learning model using direct learning methods. This type of research uses experimental research with a quantitative approach. The research population is all students of class VIII Suluun Tareran State Junior High School, the 2023/2024 school year consisting of three classes, with a total of 41 learners. Samples taken based on random sampling techniques were obtainted by students of class VIII A as an experimental class and class VIII B as a control class. The study used posttest-only control design. Student posttest results data are tested requirement, namely normality test and homogeneity test before hypothesis test. The results of the hypothesis test analysis with a real level of ???? = 0.05 obtained ????ℎ???????????????????? = 2.580 and ???????????????????????? = 2.048, then the ????ℎ???????????????????? > ???????????????????????? means reject the ????0 so that the ????1 accepted is ????1 > ????2. This it is concluded, that the average student learning outcome taught using the GBL learning model is better than the average student learning outcome taught using direct learning methods.